Divergent - Roth, Veronica (New York : Katherine Tegen Books, 2011)
In Beatrice Prior's dystopian Chicago, society is divided into five factions, each dedicated to the cultivation of a particular virtue -- Candor (the honest), Abnegation (the selfless), Dauntless (the brave), Amity (the peaceful), and Erudite (the intelligent). On an appointed day of every year, all sixteen-year-olds must select the faction to which they will devote the rest of their lives. For Beatrice, the decision is between staying with her family and being who she really is -- she can't have both. So she makes a choice that surprises everyone, including herself. During the highly competitive initiation that follows, Beatrice renames herself Tris and struggles to determine who her friends really are -- and where, exactly, a romance with a sometimes fascinating, sometimes infuriating boy fits into the life she's chosen. But Tris also has a secret, one she's kept hidden from everyone because she's been warned it can mean death. And as she discovers a growing conflict that threatens to unravel her seemingly perfect society, she also learns that her secret might help her save those she loves, or it might destroy her. Debut author Veronica Roth bursts onto the literary scene with the first book in the Divergent series -- dystopian thrillers filled with electrifying decisions, heartbreaking betrayals, stunning consequences, and unexpected romance.
In sixteen-year-old Beatrice Prior's world, society is divided into five factions Abnegation (the selfless), Candor (the honest), Dauntless (the brave), Amity (the peaceful), and Erudite (the intelligent) each dedicated to the cultivation of a particular virtue, in the attempt to form a perfect society. At the age of sixteen, teens must choose the faction to which they will devote their lives. On her Choosing Day, Beatrice renames herself Tris, rejects her family's Abnegation faction, and chooses Dauntless, the faction of daredevils and adrenaline junkies whose lives are devoted to courageousness and chasing out weakness. After surviving a brutal initiation, Tris finds romance with a super-hot, super-fearless Dauntless boy named Four, but also discovers unrest and growing conflict in their seemingly perfect society. To survive and save those they love, Tris and Four must use their strengths to uncover the truths about their identities, their families, and the order of their society itself
Keywords: COURAGE FICTION